A Tour Towards the Various Knowledge Representation Techniques for Cognitive Hybrid Sentence Modeling and Analyzer - Poonam Tanwar; T. V. Prasad; Kamlesh Dutt (Institute of Advanced Engineering and Science, 2018)
Knowledge Representation (KR) is a fascinating field across several areas of cognitive science and computer science. It is very hard to identify the requirement of a combination of many techniques and inference mechanism to achieve the accuracy for the problem domain. This research attempted to examine those techniques, and to apply them to implement a Cognitive Hybrid Sentence Modeling and Analyzer. The purpose of developing this system is to facilitate people who face the problem of using English language in daily life.